Characterisation Of Nitrate Stable Isotopes To Identify Nitrate Sources In Bukit Merah Reservoir, Perak - Yaccob, Nur Syahirah (2019)
Bukit Merah Reservoir (BMR) is known as the oldest man-made lake in Malaysia has experienced sedimentation which threatens the storage capacity and may lead to other associated problems such as eutrophication. Excessive inputs of nitrogen in water catchment may cause deterioration of the water quality. Hence, this study aims to determine the nitrate sources in water samples from BMR catchment by using nitrate stable isotopes, to assess the processes of nitrogen in the water samples and determine the local sources of goat manure, rain water, sediment and fertilizer for nitrate isotopic signature and C and N stable isotopes in sediment. The concentration of dissolved inorganic nitrogen species (NO3--N, NO2--N, NH3-N), total nitrogen (TN), phosphate (PO43-), total phosphorus (TP) and chlorophyll-a (Chl-a) were analysed using HACH DR2800 spectrophotometer. The nitrate stable isotopes (δ15N-NO3- and δ18O-NO3-) of water and the potential local sources of goat manure, sediments, rain water and fertilizer had been collected from BMR during wet and dry season and analyzed using a Trace Gas Pre-concentrator unit coupled to an isotope ratio mass spectrophotometry, (IRMS), Finnigan MAT-253. Water stable isotopes (δ2H-H2O and δ18O-H2O) in the water samples were analyzed using Picarro L2140-I isotope water analyzer. Meanwhile, carbon and nitrogen stable isotopes (δ13C and δ15N) were determined using EA-IRMS and C/ N ratio were also determined using CHN analyser in this study.